The Expansion of the Absolute Competence of Administrative Courts: A Comparative Legal Study with the French Conseil d'État - Muklis Al’anam; Lanny Ramli; Natyama Hemsanit (Universitas Negeri Surabaya, 2024)
The development of legal science is very rapid, especially in the aspect of administrative law as the first law enforcement part of other laws. So that in the theory of administrative law is inseparable from human rights, therefore the State Administrative Court is very narrow in its authority in terms of competence in handling administrative cases. Meanwhile, the Conseil d'État, which is the French administrative court, has the authority that all government actions can be disputed at the Conseil d'État. So with the concept of the idea, this research uses normative research methods with a statutory approach, conceptual approach, and comparative approach. This research examines the concept of the competence of the Conseil d'État as a measure of the expansion of competence by the Indonesian state administrative court. Thus this research will conclude the idea that it is important to amend Law No. 51/2009 on State Administrative Courts and also Article 87 of Law No. 30/2014 on Government Administration which has an open norm regarding the concept of factual actions.